ANALISIS PROGRAM SIARAN BALADA CERITA RAMADHAN DI RADIO PRAMBORS 102.2 FM JAKARTA - Intan Leliana (Universitas Bina Sarana Informatika, 2016)
The Program of Balada Cerita Ramadhan (Ramadan Story of Ballad) at Pramborradio is program of radio drama that is purposed attractively for Kawula Muda(listener). A drama radio that has the sense of fun and religious da’wah is forteenager. This research is aimed to know the process of pre-production,production, post-production, supported factors in developing a program that TheProgram of Balada Cerita Ramadhan (Ramadan Story of Ballad) is broadcastedaltogether within eight cities (beside Jakarta) and it has been starting since pastten years. Moreover, this program is popular in big cities and obtains positivefeedback from the listener, especially Prambors radio. This research of methoduses qualitative descriptive analysis. The data collection is done by doing severalsteps, such as: interview, observation, documentation review, and library. Theresult of this research is explained by seeing three processes; they are: preproduction,production, and post-production. Also, the influence for KawulaMuda is able to spend the time of ‘ngabuburit’ without visiting the target place,without giving money. Even, it is able to get the true meaning story of friendshipand positive story that can be dedicated into a certain community.